On the attitude to unnatural death in Russia of the 15th — 17th centuries: russian historiography - Irina Afanasyeva (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
This article studies the historiography of the topic of attitude to the “wrong” death in Russia in the 15th — 17th centuries. During the two hundred years of studies, a great amount of work has been done, though a number of important issues remain unclear. It has been found out that the memorial practice came to Russia with the adoption of Christianity. But alongside the Orthodox tradition of commemorating this kind of dead, there was a so-called folk practice which was diff erent from the traditional Christian practice. Scholars paid close attention to the problem of perception of unnatural death in a medieval society as a sociocultural phenomenon. This question has given rise to a discussion as to the the nature of this phenomenon and its specific manifestations. In addition, a question was raised when in Russia appeared the practice of commemorating those dead who died the “vain” death. Preliminary observations have allowed us to state that it emerged in the fi rst half of the 13th century. Among the least studied is the question of the theological component of the problem.